Adv Toxicol Toxic Effects 2020
DOI: 10.17352/atte.000009
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and interactions of priority heavy metals with some antioxidant micronutrients in inhabitants of a lead-zinc mining community of ebonyi state, Nigeria

Abstract: Background: Human exposure to xenobiotics, especially priority heavy metals (lead, cadmium, arsenic, mercury and chromium), is unavoidable because of their involvement in industrial applications, accumulation in the environment over time and non-biodegradability. Unfortunately, they induce unprecedented biochemical and pathological changes on those exposed to them, causing oxidative damages and organ toxicities. Aim: This study investigated the frequencies of priority heavy metals and their impact on some micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Determination of serum electrolyte levels is important in assessing the tubular integrity of the nephron (Bagga et al 2005) . It has been reported that mineral levels are affected due to nephrotoxicity caused by some heavy metals (Tilako et al 2020). It was reported that sodium arsenite administration in rats caused significant increases in serum K + (Ewere et al 2019, Sharma et al 2022, and Cland Na + (Ewere et al 2019) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of serum electrolyte levels is important in assessing the tubular integrity of the nephron (Bagga et al 2005) . It has been reported that mineral levels are affected due to nephrotoxicity caused by some heavy metals (Tilako et al 2020). It was reported that sodium arsenite administration in rats caused significant increases in serum K + (Ewere et al 2019, Sharma et al 2022, and Cland Na + (Ewere et al 2019) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Human exposure occurs through consumption of contaminated food and water, inhalation of polluted air, smoking cigarettes (Domingo-Relloso et al, 2020), and definitely through occupation (Azeh Engwa et al, 2019). Heavy metal pollution in proximity to industries was reported to alter antioxidant activities and other biological functions of micronutrient in both occupationally exposed and environmentally exposed subjects (Bello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%